The Role Of The Padang Ati Religious Community In Enhancing The Social Spirituality Of The Peripheral Community In Purwoasri, Tegaldlimo, Banyuwangi - Ilham Nur Kholiq; Nurul Inayah (Simfoni Ilmu Cindekia, 2025)
In the pandemic era, the spiritual values of society have begun to erode due to economic, religious, and educational aspects. The Padang Ati religious community is undertaking a movement to maintain the balance of spiritual and social values. The goal of this movement within the community is to preserve the existence of spiritual and social values. The method of this service is to train and enhance spiritual activities, provide Islamic studies, and train social activities.The Padang Ati religious community is a group that helps the outskirts of the Purwosri Tegaldlimo village community in realizing a complete human being, starting from spiritual and social aspects. The activities carried out by the community include reciting sholawat as a way to express love for the Prophet, performing special prayers for education and strengthening faith, Islamic studies on fiqh, tauhid, and dhikr as a form of spiritual education to become better individuals, and ending with social activities such as providing food aid. Those activities were initiated due to the pandemic situation, where the outskirts community of Purwoasri certainly needed assistance to recover from the condition. The Padang Ati community activities are held every forty days or every nine days on Wednesday nights.